The Study of Medical Scientific Products of Iran in Web of Science: Literature Review - Sokaineh Falsafin; Samaneh Khavidaki; Mahdi Mohammadi (Tehran University of Medical Sciences, 2019)
Background and Aim: The purpose of this study is the analysis of articles published about the evaluation of medical scientific products in Web of Science database. Materials and Methods: This is a quantitative research that is based on literature review. The population of the study consists of 55 articles published in valid national scientific journals on the review of medical scientific products of Iran in Web of Science. Results: The findings show that during 2006-2016, about 35 articles reviewed the scientific outputs of medical universities and the others examined the scientific outputs of a particular subject area, among which pharmaceutical and surgical fields had the most studies. Some 60.6% of the studies were published by specialists in the field of knowledge and information science, and 39.4% by medical specialists. Among universities, Iran University of Medical Sciences, and among individuals, Hafez Mohammad Hassanzadeh Asfijani were recognized as the most prolific. Most researches have been published using Scientometric Approach, and among scientific software, Pajek has been used more. Among the published articles, those with two and three authors were the most. Conclusion: The articles have been quantitative, and mentioning various methods indicates a kind of confusion in the choice of vocabulary and terminology.